(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The ultimate valuable equities of an organization are labourers. Employees are the ones who are solely responsible for the efficacious operating of an establishment. The most significant point to be successful in present day’s combative world in any profession absolutely depends on consumer satisfaction. As an outcome, the utmost prerogative for many organizations has been satisfying the needs of customer. Although regardless of contentment of the laborers, the employees are the internal consumer of the establishment. The foremost resources of any of the organization are the employees. The enterprise which is swamped with grievances has its ramifications on the fecundity of employees. It automatically leads to negative impacts on overall productiveness of the company. The focal intention of this research is to rummage upon the employee grievances in co-operative sugar mills.